1996
DOI: 10.1074/jbc.271.23.13584
|View full text |Cite
|
Sign up to set email alerts
|

Human Fatty-acid Synthase Gene

Abstract: We have isolated and sequenced a genomic clone coding for the first three exons and the 5'-flanking region of the human fatty-acid synthase gene. The translation initiation site, ATG, is located in exon II. Primer extension and S1 nuclease analyses showed the presence of three transcription initiation (Ti) sites: Ti I, Ti II, and Ti III. The Ti I site is mapped to the beginning of the untranslated exon I and preceded by a promoter with recognizable TATA and CAAT boxes. The Ti II and Ti III sites are located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
2
25
1
1
Order By: Relevance
“…This motif is found in the promoter of glyceraldehyde-3-phosphate dehydrogenase gene (39). At position Ϫ198, the sequence closely matched that of the fat-specific element 1 (FSE1) of the fatty acid synthase gene (TCAGGGCCCAGGAACTG) (40). The presence of the FSE1 in the proximal promoter suggested that this promoter may mediate the transcripts that are used under lipogenic conditions as we have previously shown that these transcripts were detected in both abdominal and epididymal fat tissues (17).…”
Section: Organization Of the Coding Exons-mentioning
confidence: 81%
See 1 more Smart Citation
“…This motif is found in the promoter of glyceraldehyde-3-phosphate dehydrogenase gene (39). At position Ϫ198, the sequence closely matched that of the fat-specific element 1 (FSE1) of the fatty acid synthase gene (TCAGGGCCCAGGAACTG) (40). The presence of the FSE1 in the proximal promoter suggested that this promoter may mediate the transcripts that are used under lipogenic conditions as we have previously shown that these transcripts were detected in both abdominal and epididymal fat tissues (17).…”
Section: Organization Of the Coding Exons-mentioning
confidence: 81%
“…FSE1 has been shown to be involved in the regulation of genes whose expression is closely linked to adipocyte differentiation. These include the putative fatty acid binding protein (ap2) (41), glyceraldehyde-3-phosphate dehydrogenase (42), adipsin, acyl-CoA synthetase, fatty acid synthase (40). There were also eleven copies of the unusual motif, TCCCC or TCCCCC arranged as direct or inverted repeats (boxed) (Fig.…”
Section: Organization Of the Coding Exons-mentioning
confidence: 99%
“…The anti-SREBP1a [the N-terminal domain of SREBP (amino acids 1-520)] and the anti-Sp-1 antibodies were purchased from Santa Cruz Biotechnology, and the anti-NF-Ya antibodies were purchased from PharMingen. The sources of all the other chemicals, radioactive materials, and DNA-modifying enzymes were as described (33,34). The oligonucleotides were purchased from Integrated DNA Technologies (Coralville, IA).…”
Section: Methodsmentioning
confidence: 99%
“…The human FAS promoter I-luciferase plasmids LC9-2, LC9-3, LC9-4, LC9-5, and LC11 and the TK-luciferase plasmids TK-272͞-67 and TK-272͞-40 were constructed as described (33,34). LC9-2͞del was generated by deleting the SmaI fragment (nucleotides Ϫ110 to Ϫ40) from LC9 -2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation